Hubungan Tingkat Kecemasan Terhadap Kinerja Dosen dan Karyawan Universitas Muhammadiyah Bengkulu di Masa New Normal Covid 19 - Fatsiwi Nunik Andari; Nurhayati Nurhayati; Andri Kusuma Wijaya; Juli Andri (LPPM Universitas Muhammadiyah Riau, 2022)
Corona virus disease (Covid-19) which was first discovered in Wuhan, China was declared a pandemic. WHO recorded 213 countries affected by Covid-19 cases. The number of additional new cases confirmed positive and the number of deaths in one day continues to increase, including in Bengkulu Province. The high incidence of Covid-19 cases raises anxiety for everyone, including lecturers and employees of the Muhammadiyah Bengkulu University. The purpose of this study was to determine the relationship between anxiety level and performance of lecturers and employees Muhammadiyah Bengkulu University who worked during the new normal Covid-19 period. This research uses a cross sectional design. The total sample was 90 people. Data collection was carried out using the Zung Self Anxiety Rating-Scale (ZSAR-S) questionnaire and the Individual Work Performance Questionnaire (IWPQ) questionnaire. The results of this study indicate that 87.8% of respondents had a mild anxiety level and 70% of respondents had a moderate level of performance. Based on the Spearman Rank statistical test, there was no significant correlation between the anxiety level and performance of lecturers and employees Muhammadiyah Bengkulu University of while working during the new normal Covid-19 period with p-value = 0.855. The conclusion of the study is there is not a relationship between anxiety level and the performance of lecturers and employees Muhammadiyah Bengkulu University in new normal Covid-19 period.